Risk Calculation to Propose Disaster Management for Shafira Corporation's Enterprise Resource Planning - Fandhiny, Vanny; Ratnaningtyas, Sudrajati (Journal of Business and Management, 2015)
Abstract. Shafco is the pioneer of Muslim fashion industry that has survived for 26 years and became the largest in Indonesia. It is not inndependent of the technology support in helping Shafco grow and survive. The last four years Shafco choose to develop ERP technologies based on open source. But behind the success Shafco if you see the location of its headquarters located in the eastern Bandung area, there is a risk to threats and disasters since the region was recorded as the Bandung basin area which is prone to cyclones. In this research will try to help Shafco in making disaster management in the descriptive case study format by using the formula environmental risk assessment. Risk analysis results along with the results of observational data and interview, will be used as a benchmark manufacture of disaster management in Shafira. With the same formula will be two approaches to get the value of the risk that in a ratio approach between the receptor and the nominal approach in rupiah. The first is looking for the probability of occurrence of hazards, distinguished for threats from nature that is processed from the data BNPB and to the threat of technological processing of questionnaire data using simple probability calculations. To get the value of the consequences will be different on each approach. Consequences in the comparative approach depend on value for each receptor and to approach the nominal, the consequences of the unit will be expressed in rupiah obtained from the estimated average salary of employees per day multiplied by the number of days of recovery to the threat from human activities and to threats from nature will be used for estimated losses on assets experienced in case of disaster. The current disasters that occurred at Shafira are divided into two categories: natural hazard, in particular whirlwinds (Tornado); and technological including nature-to-technological hazard which flood and blackout (light off) and human-to-technological hazards such mistaken input data and mistaken delete data. The results of calculations using the ratio approach shows that the greatest risk is from the activity of employee negligence, then tornadoes, floods and lastly due to a light off. Meanwhile, when measured using a nominal approach, the risks of large losses are due to floods, tornadoes, off the lights and the last is due to the activity of employee negligence.Â Keyword: Disaster Management, Enterprise Resource Planning, Hazard, Probability, Environmental Risk assessment